Barriers in the Development of Small Businesses in Kosovo - GASHI, Shaip (Theoretical and Practical Research in Economic Fields, 2024)
The research aims to identify barriers to the growth of entrepreneurship in the country and assess their real impact on the ability of businesses to operate. The main research methods used were analysis, forecasting, abstraction, and statistical methods. As part of the study, the results of a survey conducted in Kosovo were presented, which allowed us to understand the views of business owners and managers on the obstacles to business growth in Kosovo. A majority of respondents were found to see significant obstacles to doing business in Kosovo. These barriers harm their business opportunities and plans for future business operations. In addition, more than two-thirds of the surveyed business owners and managers expressed a desire to develop their business in the future, while the rest did not. The survey also identified several factors that negatively affect business in Kosovo. Among them were poor access to finance, problems in tax policy, lack of rule of law, infrastructure development. This study provides valuable insights into the challenges and intentions of businesses in Kosovo, shedding light on the factors that influence business growth and development. The findings can be used both in shaping the government’s business policy and by the managers of such companies in formulating their development strategies.